Personality traits in patients with neuroepithelial tumors: a prospective study - Gempt, Jens; Schirmer, Lucas (Scientific reports, 2018)
Aim of this study was to analyze personality traits in patients with neuroepithelial brain tumors. Personality alteration is a common feature in brain tumor patients, but not much is known about associations between specific personality changes and brain tumors. We assessed potential factors influencing personality such as tumor location, tumor grade and tumor volume. Mini-mental state examination (MMSE), Beck’s Depression Inventory II (BDI-II), and the NEO Five-Factor Inventory (NEO-FFI) for the five factors of personality were acquired. Patients had lower scores regarding the factor openness and higher scores regarding the BDI-II compared to the norm population. No significant influencing factors (tumor entity, location) were found regarding personality traits. Neuroticism was associated with depression, whereas extraversion showed an opposed association. Patients with intrinsic brain tumors have differences in personality traits compared to the control population, with an emphasis on the factor openness. No significant confounding factors like tumor grade, entity, or location were found for personality traits.